Long‐term prognosis and risk factors among patients with HPV‐associated oropharyngeal squamous cell carcinoma. Issue 19 (16th July 2013) - Lin, Brian M.; Wang, Hao; D'Souza, Gypsyamber; Zhang, Zhe; Fakhry, Carole; Joseph, Andrew W.; Drake, Virginia E.; Sanguineti, Giuseppe; Westra, William H.; Pai, Sara I.
<x xml:space="preserve">Abstract</x> BACKGROUND A subset of patients with human papillomavirus (HPV)‐associated oropharyngeal squamous cell carcinoma (HPV‐OSCC) experience poor clinical outcomes. The authors of this report explored prognostic risk factors for overall survival (OS) and recurrence‐free survival (RFS). METHODS Patients with incident HPV‐OSCC who received treatment at the Johns Hopkins Hospital between 1997 and 2008 and who had tissue available for HPV testing as well as demographic and clinicopathologic information (N = 176) were included. Tissue was tested for HPV by in situ hybridization (ISH) and/or p16 immunohistochemistry. Demographic and clinicopathologic information was extracted from medical records. RESULTS In total, 157 of 176 patients (90%) with OSCC had HPV‐associated disease (HPV‐OSCC). In the patients with HPV‐OSCC, the 3‐year and 5‐year OS rates were 93% (95% confidence interval [CI], 88%‐98%) and 89% (95% CI, 81%‐97%), respectively. Shorter survival was observed among older patients (hazard ratio [HR], 2.33 per 10‐year increase; 95% CI, 1.05‐5.16 per 10‐year increase; P = .038), patients with advanced clinical T classification (HR, 5.78; 95% CI, 1.60‐20.8; P = .007), and patients who were currently using tobacco (HR, 4.38; 95% CI, 1.07‐18.0; P = .04). Disease recurrence was associated with advanced clinical T‐classification (HR, 8.32; 95% CI, 3.06‐23; P < .0001), current/former alcohol use (HR, 13; 95% CI, 1.33‐120; P = .03), and unmarried status (HR, 3.28; 95% CI, 1.20‐9.00; P = .02). Patients who remained recurrence free for 5 years had an 8.6% chance of recurrence by 10 years (1‐sided 95% CI upper bound, 19%; P = .088). CONCLUSIONS In this study, prognostic risk factors were identified for patients with HPV‐OSCC. The observed recurrence rates between 5 years and 10 years after definitive therapy need to be validated in additional studies to determine whether extended cancer surveillance is warranted in this cancer population. Cancer 2013;119:3462–3471.. © 2013 American Cancer Society.